High Division of the Median Nerve with Unusually High Origin of the 3rd Space Common Digital Nerve. (December 2020) - Kadar, Iuliu Alpar; Virág, Timea Helga; Matei, Ileana Rodica; Georgescu, Alexandru Valentin
Highlights: Encountering rarely documented median nerve variants increases the risk of iatrogenic injury. High origin of the third common digital nerve with trans-muscular course through the flexor digitorum superficialis muscle. An additional subgroup within group 3 of the Lanz classification can be added, namely 3D. Abstract: Background: Median nerve (MN) variation in the carpal tunnel has been well documented by Lanz. Encountering rarely documented variants, that do not fit into existing classifications, increases the risk of iatrogenic injury. Methods: The random occurrence of two unclassifiable anatomical variants of the MN in the carpal tunnel gives motivation to search the literature for similar and identical cases. Case reports: This article presents two cases of very rare anatomical variants of high division of the MN. First case is a pure high branching of the 3rd space common digital nerve (CDN). The second case is a high division of the MN to a thicker lateral component and a thinner medial component. The lateral component of the MN gives off the palmar cutaneous branch (PCB), the thenar motor branch (TMB), the 1 st and 2 nd space CDN's and contributes medially with a branch to the 3 rd space CDN. The medial component of the MN bifurcates distally into a medial and lateral branch. The lateral branch from the medial component of the MN distally unites with the medial branch of the lateral component of the MN to form the 3 rd space CDN. The medial branch from the medial component of the MN has a major contribution to the 4 th space CDN from the ulnar nerve. In both cases, the medial component of the MN has a transmuscular course through the flexor digitorum superficialis (FDS) muscle. Discussion: Finding similar case reports from worldwide suggests the need to improve current classification of the MN variants in the carpal tunnel. Conclusions: One cannot rely entirely on the existing anatomical classifications of the MN in the carpal tunnel. There is an underappreciated risk of iatrogenic injury, especially in endoscopic carpal tunnel release, and a chance of missing out on repair of important anatomical structures in trauma cases. There is a possibility of augmenting group 3 of Lanz's classification by adding subgroup "3D High division of the MN with the medial component having a transmuscular course through the FDS muscle", stating the different distal branching patterns.